A field guide to awkward silences - Petri, Alexandra (New American Library, 2015)
"Washington Post columnist Alexandra Petri turns her satirical eye on her own life in this hilarious new memoir... Most twentysomethings spend a lot of time avoiding awkwardness. Not Alexandra Petri. Afraid of rejection? Alexandra Petri has auditioned for America's Next Top Model. Afraid of looking like an idiot? Alexandra Petri lost Jeopardy! by answering "Who is that dude?" on national TV. Afraid of bad jokes? Alexandra Petri won an international pun championship. Petri has been a debutante, reenacted the Civil War, and fended off suitors at a Star Wars convention while wearing a Jabba the Hutt suit. One time, she let some cult members she met on the street baptize her, just to be polite. She's a connoisseur of the kind of awkwardness that most people spend whole lifetimes trying to avoid. If John Hodgman and Amy Sedaris had a baby ... they would never let Petri babysit it. But Petri is here to tell you: Everything you fear is not so bad. Trust her. She's tried it. And in the course of her misadventures, she's learned that there are worse things out there than awkwardness-and that interesting things start to happen when you stop caring what people think. "--